2015
DOI: 10.1186/s40348-015-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Airway reactivity and sphingolipids—implications for childhood asthma

Abstract: Asthma is a clinically heterogeneous disorder, whose onset and progression results from a complex interplay between genetic susceptibility, allergens, and viral triggers. Sphingolipids and altered sphingolipid metabolism have emerged as potential key contributors to the pathogenesis of asthma. Orosomucoid-like 3 gene (ORMDL3) and the asthma susceptibility locus 17q21 have been strongly and reproducibly linked to childhood asthma, but how this gene is functionally linked to asthma is incompletely understood. OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
3
38
1
Order By: Relevance
“…CCL23 is an eosinophilic chemokine, that has been identified as a possible biomarker for anti-IL13 targeted therapies (49, 50). Several of these are enzymes expressed within eosinophils, such as CLC, IDO1, SMPD3 , and SPNS3 , and the latter two are both involved in the sphingolipid pathways, known to mediate airway hyperresponsiveness and mast cell activation (51, 52). Another gene CAMK1 has been implicated as an asthma control gene(20), but has not been identified previously with IgE or an allergy-related phenotype among individuals diagnosed with asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCL23 is an eosinophilic chemokine, that has been identified as a possible biomarker for anti-IL13 targeted therapies (49, 50). Several of these are enzymes expressed within eosinophils, such as CLC, IDO1, SMPD3 , and SPNS3 , and the latter two are both involved in the sphingolipid pathways, known to mediate airway hyperresponsiveness and mast cell activation (51, 52). Another gene CAMK1 has been implicated as an asthma control gene(20), but has not been identified previously with IgE or an allergy-related phenotype among individuals diagnosed with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes from our eosinophil-related gene sets have known associations with allergic asthma and may also have therapeutic or diagnostic potential, including CCL23, CLC, CEBPE, CAMK1, IDO1, SIGLEC8, SMPD3 and SPNS3. [44][45][46][47][48][49][50][51] Potential therapeutic targets include cell surface receptors, such as Siglec8, an inhibitory receptor on eosinophils with polymorphisms associated with asthma. [45][46][47] CCL23 is an eosinophilic chemokine that has been identified as a possible biomarker for anti-IL13-targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids are a class of complex lipids containing a backbone of sphingoid bases. These lipids have long been known as structural components of human cell membranes and as a component of surfactant, but have more recently emerged as signaling molecules that modulate the host immune response and contribute to the pathogenesis of respiratory diseases, such as bronchiolitis, pneumonia, and asthma [ 7 , 22 ]. While sphingolipids production is ubiquitous in eukaryotes, it is also produced by several bacteria genera such as Bacteroides , Prevotella , and Porphyromonas [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…ORMDL3 activates ATF-6α pathway during ER unfolded response and induces sarco/endoplasmic reticulum Ca 2+ ATPases pump (SERCA2b) to regulate ER-mediated Ca 2+ signaling and cellular stress response [12,13]. ORMDL3 acts as a mediator of sphingolipid homeostasis [14,15] and can also regulate eosinophil trafficking, recruitment and degranulation [16]. Studies of mice generated to express increased levels of human ORMDL3 have also demonstrated that in vivo ORMDL3 activates ATF6α (but not Ire1 or PERK), and that this is associated with increased expression of SERCA2b.…”
Section: Abstract: Asthma; Chromosome 17q21mentioning
confidence: 99%